2015
DOI: 10.1088/0952-4746/35/1/179
|View full text |Cite|
|
Sign up to set email alerts
|

Patient doses in paediatric interventional cardiology: impact of 3D rotational angiography

Abstract: The aim of this study was to calculate the contribution of 3D rotational angiography to radiation doses received by paediatric patients in a cardiac catheterisation laboratory. The percentage increase in the median value of air kerma-area product due to cone beam CT was 33 and 16% for diagnostic and therapeutic procedures, respectively. Results are presented separately for five age groups and ten weight groups. Several methods for reducing radiation from 3D rotational angiography are suggested and patient dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Recording P KA and K a,r for the cone-beam CT portion of interventional procedures, when this information is available, may be helpful in optimisation of this portion of interventional procedures (Section 5.3.3). The same is true for three-dimensional rotational angiography (Corredoira et al., 2015).…”
Section: Interventional Proceduresmentioning
confidence: 77%
See 2 more Smart Citations
“…Recording P KA and K a,r for the cone-beam CT portion of interventional procedures, when this information is available, may be helpful in optimisation of this portion of interventional procedures (Section 5.3.3). The same is true for three-dimensional rotational angiography (Corredoira et al., 2015).…”
Section: Interventional Proceduresmentioning
confidence: 77%
“…Dental and maxillofacial cone-beam CT procedures should not exceed the dose of comparable CT procedures for high-contrast objects (typical CTDI vol < 10 mGy). (232) When used to guide biopsies, cone-beam CT can reduce patient dose and improve targeting accuracy compared with conventional CT (Abi-Jaoudeh et al., 2016). Cone-beam CT is also becoming increasingly important during interventional fluoroscopy procedures (Wallace et al., 2008; Lightfoot et al., 2013; Corredoira et al., 2015). It can provide information and guidance that is not otherwise available during the procedure, and can increase the safety of the procedure (Lee et al., 2014).…”
Section: Digital Radiography Computed Tomography Nuclear Medicinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most articles reported that 3DRA also had equal [3, 9, 14, 19, 21, 24] or less contrast and radiation exposure when compared to CA, even when interventions were performed [4, 17, 18]. To add to that, some studies even indicate that the doses can be further diminished by reducing the frame rate and by getting better acquainted with the equipment [10, 22, 27]. Besides, many articles admitted to a learning curve causing higher contrast and radiation exposure at the start, which dropped after getting more familiar with the technique or after having consulted a technician from the corresponding 3DRA vendor [4, 6, 8, 9, 13, 22].…”
Section: Discussionmentioning
confidence: 99%
“…This part of the commissioning testing sets the baseline values as a reference for future routine quality control tests (constancy tests) to monitor the most significant system operation parameters to ensure their stability over time. (2,3,6) A recent study that included 756 pediatric cardiac catheterization procedures concluded that the percentage increases in the median value of the air kerma‐area product due to CBCT were 33% and 16% for diagnostic and therapeutic procedures, respectively (7) To improve optimization and properly manage patient doses with sufficient diagnostic‐quality imaging, knowledge of the equipment's performance is necessary. This report presents the results of the physical characterization conducted as part of the commissioning of a biplane angiography system dedicated to pediatric interventional cardiology (IC), including the 3D‐RA mode as one of the imaging options.…”
Section: Introductionmentioning
confidence: 99%